Single crystal growth and anisotropic physical properties of Sm4Co3Ga16. (31st July 2018) - Zhang, Y J; Xia, X B; Jiang, W B; Wang, Y F; Liu, J Y; Yuan, H Q; Lee, Hanoh
Abstract: We have synthesized high quality single crystals of Sm4 Co3 Ga16 with gallium flux and investigated its physical properties with electrical resistivity, magnetization and specific-heat measurements. Antiferromagnetic transition below 6.7 K has been detected. No superconducting transitions have been dectected down to 0.5 K from our single crystals. Based on our experimental result, Sm 3+ state in Sm4 Co3 Ga16 is likely well localized, in which stable magnetic moment in its doubly degenerated ground state contributes to the magnetic order with little interference of Kondo type of interaction.